Characteristics of loess landslides triggered by the 1927 Mw8.0 earthquake that occurred in Gulang County, Gansu Province, China - Zhong, Xiumei; Xu, Xiaowei; Chen, Wenkai; Liang, Yuxin; Sun, Qinyao (Frontiers in Environmental Science, 2022)
The 1927 Gulang Mw8.0 earthquake was one of the largest earthquakes in Gansu, China, which triggered lots of loess landslides. However, the loess of the study area is atypical and different from that in Loess Plateau. Meanwhile, there are few systematic researches on the characteristics of these seismic landslides. Combined with previous studies and field investigations, the landslide distribution has been revealed through the visual interpretation on remote sensing image of the study area. The relationships between landslides and various influencing factors have been explored by ArcGIS. Furthermore, the comparisons have been made between the Gulang earthquake landslides and other seismic landslides in Loess Plateau from multiple perspectives. 807 earthquake landslides have been interpreted, with a total landslide area of 256.14 km2. The region of Ⅹ degree is the dominant area of landslides distribution. And most landslides are distributed in slope angle of (10°,40°]. The relative elevation difference of (100m,300m] is the high-incidence range of landslides. Compared with seismic landslides in Loess Plateau, the slope angle and the relative elevation difference of most landslides in the study area are larger. The strength of loess structure in the study area is stronger than that in Loess Plateau form the view of physical properties and microstructure.